(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
During the period from November 2015 till the end of March 2016, a total of 218 fish specimens belonging to Planiliza abu from Euphrates River at Al-Hilla city and the Babil drainage networkBabylon province were inspected for parasites at Laboratory at the Al-Musaib Technical College. Two Vorticella were recorded for the first time in Iraq from skin and gills of P. abu. These were:Vorticella globulariaMüller, 1773 and Vorticella costata(Sommer, 1951). The description and measurement of this parasite as well as their measurements were given